2019
DOI: 10.1002/rcm.8543
|View full text |Cite
|
Sign up to set email alerts
|

In vitro metabolism of the synthetic cannabinoids PX‐1, PX‐2, and PX‐3 by high‐resolution mass spectrometry and their clearance rates in human liver microsomes

Abstract: Rationale N‐(1‐Amino‐1‐oxo‐3‐phenylpropan‐2‐yl)‐1‐(5‐fluoropentyl)‐1H‐indole‐3‐carboxamine (PX‐1), N‐(1‐amino‐1‐oxo‐3‐phenylpropan‐2‐yl)‐1‐(5‐fluoropentyl)‐1H‐indazole‐3‐carboxamide (PX‐2), and N‐(1‐amino‐1‐oxo‐3‐phenylpropan‐2‐yl)‐1‐(cyclohexylmethyl)‐1H‐indazole‐3‐carboxamide (PX‐3) are scheduled synthetic cannabinoids (SCs). Due to the lack of metabolism data and the extensive metabolism of SCs, consumption of these illicit substances is challenging to prove. The aim of this study was to investigate the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
(24 reference statements)
3
13
2
Order By: Relevance
“…A fluorine‐containing metabolite was identified by (Fabregat‐Safont et al (; M3); however, this metabolite is potentially shared with 5F‐MPP‐PICA (Figure ) as outlined below. M1–M4 reported in our report (non‐specific metabolites) were also identified by Cooman and Bell (); these were the only metabolites reported. Fabregat‐Safont et al identified five Phase II metabolites corresponding to the Phase I metabolites identified in their study.…”
Section: Discussionsupporting
confidence: 83%
“…A fluorine‐containing metabolite was identified by (Fabregat‐Safont et al (; M3); however, this metabolite is potentially shared with 5F‐MPP‐PICA (Figure ) as outlined below. M1–M4 reported in our report (non‐specific metabolites) were also identified by Cooman and Bell (); these were the only metabolites reported. Fabregat‐Safont et al identified five Phase II metabolites corresponding to the Phase I metabolites identified in their study.…”
Section: Discussionsupporting
confidence: 83%
“…Fragment m/z 233.11 is the unchanged fluoropentylindazole acylium ion, and removal of carboxamide group is demonstrated by m/z 352.18. For the observed product ion m/z 251.12, two structures can be considered: (a) a fluoropentylindazole acylium ion with addition of a water molecule as described by Fabregat-Safon et al [13] and (b) a dealkylation of the fluoropentylindazole acylium ion with a shift of the phenyl group to the second indazole nitrogen as described by Cooman et al [11]. Since a shift of the phenyl group to the second indazole nitrogen was considered to be less likely than the addition of water, configuration (a) was concluded for the first structure.…”
Section: Characteristic Fragments Of Px-2mentioning
confidence: 99%
“…The number of phase I metabolites which they found ranged from six to ten. They all found monohydroxylation of PX-1 and PX-2 and also further hydroxylations, such as dihydroxylation, amide hydrolysis, carboxylation and dealkylation [11][12][13]; monohydroxylation, oxidative defluorination, and defluorination with subsequent carboxylation [14][15][16][17][18][19][20][21][22][23][24] were the most dominant alterations. Dihydrodiol metabolites, detected for 5F-AB-PINACA and THJ-2201 were not observed for PX-1 and PX-2 [14,17,18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations